If You Know Something, Say Something: Young Children's Problem with False Beliefs - Hansen, Mikkel B. (Frontiers in Psychology, 2010)
Whether young children understand that others may hold false beliefs is a hotly debated topic in psychology and neuroscience. Much evidence suggests that children do not pass this milestone in their understanding of other people until the age of 5 years. Other evidence suggests that they understand already in their second year. This study proposes a novel account of the logic of conversations about certain mental states. By modifying the discourse accordingly, children passed three false belief tasks at 3 years of age while they failed standard false belief tasks. The results support the view that even young children construe other people in adult-like psychological terms.